Aid and development - Overton, John (John D.); Murray, Warwick E. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book provides an overview of what aid is, how it has changed over time, and how it is practiced, as well as debates about whether aid works, for whom, and what its future might be. It is an important resource for students, development workers and policy makers seeking an understanding of how aid works. The text shows how 'aid' is a contested and fluid concept that involves a wide and changing variety of policies, actors and impacts. Each chapter includes case studies, chapter summaries, discussions, weblinks and further reading, to help strengthen the reader's understanding"--
Aid : an introduction -- What is aid? -- Patterns of aid -- Trends in aid -- How is aid delivered? -- Does aid work? -- Conclusions : Futures for aid.
OCLC-licensed vendor bibliographic record.
Keywords: Economic assistance; Economic assistance -- Evaluation; Economic assistance -- Case studies; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Third World Development